Universality Theorems for Some Composite Functions - Janulis, Kęstutis; Jurgaitis, Donatas; Laurinčikas, Antanas; Macaitienė, Renata (Mathematical Modelling and Analysis, 2016)
In [5], it was proved that a collection consisting from Dirichlet L-functions and periodic Hurwitz zeta-functions is universal in the sense that the shifts of those functions approximate simultaneously a given collection of analytic functions. In the paper, we prove theorems on the universality of composite functions of the above collection.